Cellulolytic fungi modify the nitrogen, phosphorus, and potassium contents of organic fertilizers. Issue 1 (1st February 2022) - Fikrinda, F; Marlina, M; Khalil, M
Abstract: Cellulolytic fungi are involved in releasing nutrients from organic sources. The objective of this study was to determine the effect of cellulolytic fungi on the total nitrogen (N), total phosphorus (P), and total potassium (K) contents in different organic fertilizers. This study was arranged in randomized block design 3 X 3 with three replications. There were two factors, cellulolytic fungi ( Talaromyces pinophilus strain MR107, Penicillium sp. isolate SR18, and Purpureocillium lilacinum isolate PIGD23i) and organic fertilizers (cow manure, compost, and vermicompost). The results indicated that Penicillium sp. isolate SR18 had a better effect than other cellulolytic fungi species on tot. N, tot. P and tot. K contents of cow manure; tot. N and tot. K contents of compost; and tot. P content of vermicompost while P. lilacinum isolate PIGD23i showed a better effect on tot. N and tot. K contents of vermicompost. The highest tot. N, and tot. K contents were found in P. lilacinum isolate PIGD23i-inoculated vermicompost while the tot. P content was in Penicillium sp. isolate SR18-inoculated vermicompost. Overall, adding cellulolytic fungi is an alternative way to improve the nutrient content of organic fertilizer.